The Use of CAMELS Model to Evaluate Banks -Case Study of Several Commercial Banks in Algeria- - ABDELAZIZ SALAH EDDIN (جامعة المسيلة, 2020)
This study aims to determine the possibility of using the CAMELS model in evaluating the performance of commercial banks in terms of identifying strengths and weaknesses. The study is divided into two parts: the first part is the theoretical part of the study and second part is the fieldwork of the study. In the theoretical part, the study discussed all the aspects of the performance, financial performance, financial statement, financial statements analyses, concept of appraisal and Bank performance appraisal. The study basically divided the field work into two-parts part, number one introduce the performance of banks chosen two of them are public Banks which are the external Bank of Algeria and the National Bank of Algeria the other two are private Banks which are AL-Salam bank and AL-Baraka bank. Part number two is the evaluation of the elements of the financial statement of each bank during the period (2012-2017) and measure Banks performance using CAMELS model financial ratios. The study found that the financial analysis of the financial statements, using standard models in measuring performance, gives outputs that shows the financial analyst the current performance of the bank, and gives him the ability to visualize the future status of this performance. And All banks rely on a strategy to diversify their deposit portfolio to avoid liquidity risks. The values of net profit after taxes in banks have fluctuated continuously throughout the study period, between stability and the rise and fall in their value. All banks adopt a strategy to diversify their deposit portfolio to avoid liquidity risk. The values of net profit after taxes in banks fluctuated continuously throughout the study period between stability and rise and fall in its value. All the banks of the study sample succeeded in exceeding the standard set for the capital adequacy ratio, while there is a variation in the results of the outputs of the rest of the CAMELS model, both for public and private banks. The study recommended that Banks' administrations must rely on performance measurement standards in general and CAMELS model, in particular, to verify the reality of their performance and find out the weaknesses to avoid them in the future. The bank should focus on the credit worthiness of the client rather than focusing on the guarantees that the client offer. Banks should diversify their investment portfolios according to the scientific standards, as Markowitz standard for diversification. Imposing laws that would raise the quality of loans granted by banks and move away from financial purification operations that the government often undertakes in favor of public banks. تهدف هذه الدراسة الى تحديد إمكانية استخدام نموذج CAMELS في تقييم أداء البنوك التجارية من حيث تحديد نقاط القوة ونقاط الضعف. اعتمدت الدراسة على المنهج الوصفي التحليلي مع استخدام أسلوب دراسة الحالة، حيث قسمت الدراسة إلى فصلين، تضمن الفصل الاول الإطار النظري للأداء المالي والقوائم المالية، تحليل القوائم المالية، الأداء البنكي وتقييم الأداء البنكي. أما الفصل الثاني فهو عباره عن الجانب التطبيقي للدراسة والذي اشتمل على الدراسة التطبيقية، تم من خلالها عرض للبنوك عينة الدراسة والمتمثلة في بنكين عموميين، بنك الجزائر الخارجي والبنك الوطني الجزائري، وبنكين من البنوك الخاصة هما بنك السلام وبنك البركة. تم عرض وتحليل تطور عناصر القوائم المالية خلال الفترة (2012-2017)، وفي الأخير قياس أداء البنوك الأربعة باستخدام النسب المالية التي يشملها نموذج CAMELS. توصلت الدراسة إلى أن التحليل المالي للقوائم المالية، باستخدام نماذج قياسية في قياس الأداء، تعطي مخرجات توضح للمحلل المالي الأداء الحالي للبنك، وتمنحه القدرة على تصور الوضع المستقبلي لهذا الأداء، حيث تعتمد جميع البنوك على استراتيجية لتنويع محفظتها من الودائع لتجنب مخاطر السيولة. في حين تذبذبت قيم صافي الربح بعد الضرائب في البنوك بشكل مستمر طوال فترة الدراسة بين الاستقرار والارتفاع والانخفاض في قيمتها. كما أن كل البنوك عينة الدراسة نجحت في تجاوز المعيار المحدد لنسبة كفاية رأس المال، في حين أن هناك تباينا في نتائج مخرجات باقي معايير نموذج CAMELS سواء للبنوك العمومية والخاصة. وعليه أوصت الدراسة بـضرورة اعتماد إدارات البنوك على معايير قياس الأداء بشكل عام ومعايير CAMELS بشكل خاص للتحقق من واقع أدائها ومعرفة نقاط الضعف لتجنبها في المستقبل. وأن يركز البنك على الجدارة الائتمانية للعميل بدلاً من التركيز على الضمانات التي يقدمها العميل، بالإضافة إلى ضرورة تنويع البنوك لمحافظها الاستثمارية وفق المعايير العلمية، كمعيار ماركويتز للتنويع. كما توصي الدراسة بضرورة فرض الدولة لقوانين من شأنها رفع جودة القروض الممنوحة من البنوك والابتعاد عن عمليات التطهير المالي التي كثيرا ما تقوم بها الحكومة لصالح البنوك العامة.
Keywords: The performance, financial performance, financial statements, financial statements analyses,الأداء، الأداء المالي، القوائم المالية، تحليل القوائم المالية، نموذج CAMELS، البنوك التجارية، الجزائر. CAMELS model, Commercial banks, Algeria